Simple and efficient synthesis of 2-Aryl-2,3-dihydroquinolin-4(1H)-ones using silica chloride as a new catalyst under solvent-free conditions - Muthukrishnan, Murugan; Mujahid, Mohammad; Punitharasu, V.; Dnyaneshwar, D. A. (Synthetic Communications, 2010)
A mild, efficient, and high-yielding method for the synthesis of 2-aryl-2,3-dihydroquinolin-4(1H)-ones from their corresponding 2-amino chalcones using silica chloride (SiO2Cl) under solvent-free conditions is described. A series of 2-aryl-2,3-dihydroquinolin-4(1H)-ones containing both electron-donating and electron-withdrawing substituents were synthesized.
Keywords: 2-Amino chalcones; 2-aryl-2; 3-dihydroquinolin-4(1H)-ones; Microwave; silica chloride

Lithium tetrafluoroborate catalyzed highly efficient inter- and intramolecular aza-Michael addition with aromatic amines - Lad, Uday P.; Kulkarni, M. A.; Desai, Uday V.; Wadgaonkar, P. P. (Comptes Rendus Chimie, 2011)
Lithium tetrafluoroborate has been demonstrated for the first time to be an efficient catalyst in intermolecular aza-Michael addition aromatic amines to electron deficient alkenes. Suitability of the same catalyst in intramolecular aza-Michael addition leading 2-aryl-2,3-dihydroquinolin-4(1H) ones has also been described. (C) 2011 Published by Elsevier Masson SAS on behalf of Academie des sciences.
Keywords: 2-aryl-2; 3-dihydroquinolin-(4H)-1-ones; Anilines; Lithium tetrafluoroborate; Michael addition